Family and job microsystems as mediators between social integration and depression among rural-to-urban migrant workers in China: does having sons make a difference? - Shen, Guanghui; Tang, Jiayi; Fang, Juan; Huang, Jiahui; Zheng, Yawen; Wu, Liujun; Yang, Xudong; Chen, Yu-Hsin; Chen, Li (Frontiers in Public Health, 2024)
Background Rural-to-urban migrant workers are a vulnerable group at risk of developing depression. Based on the social-ecological systems theory, this study investigates the impact of the lack of social integration on depression, considering the mediating roles of migrant workers’ microsystems (family happiness and job burnout). Additionally, the study explores whether having sons influences these associations. Methods The sample of 4,618 rural-to-urban migrant workers was obtained from the 2018 wave of the China Labor Force Dynamics Survey (CLDS). All the measures in the survey exhibited good reliability, including the Center for Epidemiological Research Depression Scale (CES-D), family happiness, job burnout, and social integration. The data were primarily analyzed using a structural equation model. Results Social integration had a direct impact on depression among migrant workers. Additionally, it indirectly affected depression through the mediating roles of family happiness not job burnout. The moderating effect of having sons mainly occurred on the path from social integration to family happiness. Limitations The cross-sectional design impeded the ability to draw causal inferences. Conclusion This finding highlights the potential benefits of social integration and family happiness in promoting early prevention of depression among migrant workers. It indicates that the inclination toward having sons among migrant workers continues to impact their mental health.